Diagnostic value of the rectal ammonia tolerance test, fasting plasma ammonia and fasting plasma bile acids for canine portosystemic shunting. Issue 3 (June 2015) - van Straten, G.; Spee, B.; Rothuizen, J.; van Straten, M.; Favier, R.P.
Highlights: An increase in both FBA and FA is sufficient for diagnosing PSS. A negative ATT rules out PSS in a symptomatic dog. PSS in symptomatic dogs is virtually excluded when FBA is not increased. For screening, FBA alone is sufficient to exclude the presence of PSS. Blood ammonia at 20 min as part of the ATT has no additional benefit. Abstract: Portosystemic shunting (PSS) often results in hyperammonaemia and, consequently, hepatic encephalopathy. This retrospective study evaluated the sensitivity, specificity, positive and negative predictive values (PPV and NPV, respectively) and other test performance metrics for the ammonia tolerance test (ATT), serum fasting bile acids (FBA), serum fasting ammonia concentration (FA), and combinations of these tests for their association with PSS in dogs. Medical records of 271 dogs suspect for PSS (symptomatic group) and 53 dogs returning for evaluation after surgical closure of a congenital PSS (CPSS post-surgical control group) were analysed. In the symptomatic group, ATT at 40 min (T40), and the FBA had the highest sensitivity (100% and 98%, respectively) and NPV (100% and 96%, respectively) for PSS. The combination of increased FBA and FA had the highest specificity (97%), with a PPV of 97%, and a positive likelihood ratio of 29. In the CPSS post-surgical control group, the specificity and PPV of FA and the combination of increased FBA/FA were both 100%. In purebred populations, the NPV of all tests was 100%. Consequently, PSS would be ruled out in a symptomatic dog with normal FBA or ATT (T40) and would be highly probable when both FBA and FA are increased. Increased FA was conclusive for PSS in dogs evaluated for post-surgical closure of a CPSS. FBA was the most suitable test for screening purposes.